Staggered tiled and stacked positive electrode material precursor, preparation method thereof, lithium ion battery, positive electrode material and lithium battery equipment
Through the precursor of the cathode material with a dislocation flat stacked structure and the continuous co-precipitation reaction process, the stability and cost problems of high-nickel ternary cathode material are solved, and high cycle stability and low-cost production are achieved.
Patent Information
- Application Number
- CN202311422256.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-30
- Publication Date
- 2025-05-02
AI Technical Summary
The stability and safety of high-nickel ternary cathode materials are poor, resulting in poor cycle stability performance and difficult to mass production. At the same time, the continuous process costs are high and difficult to optimize.
The precursor of the positive electrode material that is stacked with dislocation tiling is stacked with dislocation tiling on the surface of the secondary particles by a plurality of sheet-shaped primary particles to form a larger stress area and improve structural stability. Through the continuous co-precipitation reaction process, a high-pressure density and structurally stable precursor was prepared.
The cycle stability and capacity performance of the cathode material are improved, mass production is achieved, and production costs are reduced through continuous processes.
Smart Images

Figure CN119920845A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium batteries, and in particular to a staggered and flat-stacked positive electrode material precursor and a preparation method thereof, a lithium-ion battery, a positive electrode material, and a lithium battery device. Background Art
[0002] High-nickel ternary cathode materials are high-capacity lithium-ion battery cathode materials developed in recent years. They have the important advantage of high specific capacity. However, the higher the nickel content in the ternary cathode materials, the worse the stability and safety of the materials. The structure and physical and chemical properties of high-nickel ternary cathode materials are inherited from their raw materials, high-nickel ternary cathode precursors. In the preparation process of high-nickel ternary cathode precursors, due to the high nickel content, the precipitation rate is fast, and the continuous process has a short residence time, which is easy to generate fine radial fine needle grain morphology. High-nickel ternary cathode materials and their precursors with large and medium particles of 6-20μm are prone to cracking. Although the battery materials finally prepared have high specific capacity, they have poor cycle stability and are difficult to mass produce. At the same time, the cost optimization of lithium-ion battery materials is also a core manifestation of important competitiveness in the future. The continuous process is simpler to operate than the intermittent process, and can achieve continuous feeding and discharging, saving costs.
[0003] Therefore, developing a high-nickel ternary cathode precursor product with high compaction density, stable structure and not prone to cracking can further improve its cycle performance while retaining high capacity. It is also particularly important to develop a high-nickel ternary cathode precursor preparation method that absorbs the characteristics of the continuous process, can be continuously produced, and has a low cost. Summary of the invention
[0004] The purpose of the present application is to provide a staggered and flatly stacked positive electrode material precursor and a preparation method thereof, a lithium-ion battery, a positive electrode material and a lithium battery device to solve at least one of the above problems.
[0005] To achieve the above objectives, this application adopts the following technical solutions:
[0006] A positive electrode material precursor, wherein the secondary particles of the positive electrode material precursor are formed by agglomerating a plurality of primary particles, the primary particles on the surface of the secondary particles are in a flaky shape, and the surface of the secondary particles comprises a plurality of flaky primary particles that are staggered and stacked.
[0007] The flaky primary particles on the surface mentioned above may be single-layer or multi-layer. Multi-layer primary particles are composed of multiple single-layers with the same shape and neatly stacked up and down.
[0008] Optionally, in the positive electrode material precursor, the average roundness of the cross section of the secondary particles is not less than 0.95;
[0009] In some embodiments, the average circularity is measured in a cross-sectional photograph of the secondary particles along the diameter direction at a magnification of 3000-5000 times.
[0010] Optionally, the cathode material precursor satisfies at least one of the following conditions:
[0011] A. The primary particles on the surface of the secondary particles are in the form of flakes, and the thickness of the primary particles on the surface is less than 60 nm;
[0012] B. The average angle γ between the primary particles on the surface of the secondary particles and the tangent plane of the sphere of the secondary particles is ≤10°;
[0013] C. When the width of the notch at the edge of the cut surface of the secondary particle is b, the maximum depth of the notch at the edge of the cut surface of the secondary particle is h≤0.5b;
[0014] D. The secondary particles have pores inside, and the pore diameter is ≤30 nm;
[0015] E. The secondary particles are densely arranged inside, and the porosity of the secondary particles is 2%-6%;
[0016] Optionally, the secondary particles are densely arranged in a non-radial manner.
[0017] Optionally, the cathode material precursor satisfies at least one of the following conditions:
[0018] (1) The BET of the cathode material precursor is 16-20 m 2 / g;
[0019] (2) The TD of the positive electrode material precursor is 2.2-2.5 g / cm 3 ;
[0020] (3) (D90-D10) / D50 of the positive electrode material precursor is 1.2-1.8; the particle size D50 of the positive electrode material precursor is 10-20 μm;
[0021] (4) The chemical formula of the positive electrode material precursor is Ni a M 1-a (OH)2, wherein 0.9≤a<1, M is at least one of Co, Mn, Al, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb, and Sr; preferably, M is Zr.
[0022] The present application also provides a method for preparing the positive electrode material precursor, comprising:
[0023] Adding a metal salt solution including a nickel salt and / or a doped metal salt, a precipitant and a complexing agent into the first base solution, and performing a first continuous coprecipitation reaction under an inert atmosphere to obtain a seed crystal;
[0024] The seed crystal, the precipitant and the complexing agent are added to the second base liquid, and a second continuous co-precipitation reaction is carried out under an inert atmosphere, and the positive electrode material precursor is obtained by post-processing.
[0025] Optionally, the method for preparing the positive electrode material precursor satisfies at least one of the following conditions:
[0026] a. The total metal ion concentration of the metal salt solution is 1-5 mol / L;
[0027] b. The metal salt includes one or more of sulfate, nitrate, acetate, and chloride; the ratio of nickel to the total molar amount of the metal in the metal is (0.9-1):1;
[0028] c. The doping metal M in the doping metal salt includes at least one of Co, Mn, Al, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb, and Sr;
[0029] d. The doped metal salt is a zirconium salt, and a buffer is added to the zirconium salt, wherein the buffer comprises sodium citrate and / or trisodium citrate;
[0030] e. The complexing agent comprises one or more of ammonia, ammonium bicarbonate, and ammonium carbonate, and the concentration of the complexing agent is 2-20 mol / L; the complexing agent is preferably ammonia;
[0031] f. The precipitant comprises one or more of sodium hydroxide, potassium hydroxide and lithium hydroxide, and the concentration of the precipitant is 2-20 mol / L;
[0032] g. The first base liquid and the second base liquid are each independently water or a mixed aqueous solution containing the complexing agent and the precipitant.
[0033] Optionally, the method for preparing the positive electrode material precursor satisfies at least one of the following conditions:
[0034] h. The seed crystal particle size D50 is 2-8 μm;
[0035] i. The ratio of the seed crystals added is 0.5wt%-5.0wt% of the yield of the second continuous coprecipitation reaction;
[0036] j. The temperature of the first continuous coprecipitation reaction and the second continuous coprecipitation reaction are independently 35-75°C, and the stirring speed is 200-1200r / min;
[0037] k. The pH value of the first continuous coprecipitation reaction is 11.4-12.4; the pH value of the second continuous coprecipitation reaction system is 11.0-12.0;
[0038] 1. The post-treatment includes washing, solid-liquid separation, solid drying and screening and demagnetization treatment.
[0039] The present application also provides a lithium-ion battery positive electrode material, the raw material of the lithium-ion battery positive electrode material includes the positive electrode material precursor.
[0040] The present application also provides a lithium-ion battery, comprising the lithium-ion battery positive electrode material.
[0041] The present application also provides a lithium battery device, comprising the lithium-ion battery.
[0042] Compared with the prior art, the beneficial effects of this application include:
[0043] The present application provides a positive electrode material precursor with offset tiling and stacking, the surface of the secondary particles of which is formed by multiple flaky primary particles being offset and stacked along the non-radial direction of the secondary particles, so that the secondary particles have a larger force-bearing area, and can quickly transfer the force to the primary particles in the lower layer when subjected to force, thereby solving the problem of easy cracking of the secondary particle balls. The product prepared by the present application has excellent performance, and has improved the cycle stability of the material without reducing the nickel content to ensure the specific capacity of the material, and has achieved mass production.
[0044] The higher the average roundness of the cross-section of the offset-tiled stacked precursor secondary particles prepared in the present application, the fewer the primary particle stacking defects on the surface of the secondary particles, the better the structural stability, and the more effective it is in suppressing cracks when the positive electrode material precursor is under pressure, thereby improving the cycle performance. Controlling the size of the notch at the edge of the cross-section is to control the primary particle stacking defects on the surface of the secondary particles from another dimension, suppressing cracks when the positive electrode material precursor is under pressure, thereby improving the cycle performance.
[0045] In addition, compared with the radial structure of secondary particle spheres, the present application has a structure in which the secondary particle spheres have staggered flat growth on the surface and non-radial dense arrangement inside. The stress is concentrated at the junction of the core-shell interface rather than in the radial direction of the secondary particle spheres, which improves the stress distribution, effectively buffers the volume expansion of the material during charging and discharging, improves the radial cracking problem of secondary particles, and is also more conducive to inhibiting cracking on the surface of secondary particles and corrosion and pulverization due to electrolyte infiltration, thereby improving the cycle performance of the material.
[0046] The preparation method of the staggered, flatly stacked positive electrode material precursor provided in the present application can continuously prepare products with wide particle size distribution and high compaction density. Based on the microscopic morphology of the material, the seed crystals obtained by the first continuous coprecipitation reaction are added to the second base liquid, and the secondary particles formed by the second continuous coprecipitation reaction have primary particles on the surface that grow in a staggered, flat manner, which can effectively buffer the volume expansion of the material during charging and discharging, improve the problem of radial cracking of particles, and improve the cyclic stability of the material. The preparation method uses a seed crystal process and can also avoid the problem of excessive battery micropowder due to primary nucleation.
[0047] The staggered and flatly stacked lithium-ion battery positive electrode material provided in the present application has a high average roundness of the cross-section of the secondary particles, and the edges of the cross-section have smaller gaps than complete ones, indicating that the primary particles on the surface of the secondary particles have fewer stacking defects, so that the surface of the secondary particles has good smoothness (small surface unevenness), and its structural stability is good, which can effectively inhibit the generation of cracks when the positive electrode material precursor is under pressure, thereby improving the cycle performance.
[0048] The lithium-ion battery prepared by the staggered and flat-stacked lithium-ion battery positive electrode material provided in the present application has a high capacity performance and can effectively improve the cycle performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0050] Figure 1 The SEM photo of the cross section of the secondary particles (left) and the schematic diagram of the average roundness test of the cross section of the secondary particles (right);
[0051] Figure 2 Schematic diagram of the angle between the primary particle and the tangent plane of the sphere of the secondary particle;
[0052] Figure 3 It is a schematic diagram of the test of the notch size of the cut edge of the secondary particles;
[0053] Figure 4 This is a surface SEM photo of the precursor obtained in Example 1;
[0054] Figure 5 This is a partially enlarged SEM photograph of the surface of the precursor obtained in Example 1;
[0055] Figure 6 This is a surface SEM photo of the precursor obtained in Example 2;
[0056] Figure 7This is a partially enlarged SEM photograph of the surface of the precursor obtained in Example 2;
[0057] Figure 8 This is a SEM photo of the cross section of the precursor obtained in Example 2;
[0058] Fig. 9 This is an enlarged SEM photo of the surface of the precursor obtained in Comparative Example 1;
[0059] Fig.10 This is a cross-sectional photograph of the precursor obtained in Comparative Example 1;
[0060] Fig.11 This is a surface SEM photo of the precursor obtained in Comparative Example 2;
[0061] Fig.12 This is a partially enlarged SEM photograph of the surface of the precursor obtained in Comparative Example 2;
[0062] Fig.13 The cross-sectional photograph (left picture) and the partially enlarged cross-sectional photograph (right picture) of the precursor obtained in Comparative Example 2 are shown. DETAILED DESCRIPTION
[0063] As used herein:
[0064] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0065] In these examples, parts and percentages are by mass unless otherwise indicated.
[0066] A positive electrode material precursor, wherein the secondary particles of the positive electrode material precursor are formed by agglomerating a plurality of primary particles, the primary particles on the surface of the secondary particles are in a flaky shape, and the surface of the secondary particles comprises a plurality of flaky primary particles that are staggered and stacked.
[0067] The multiple references in this application refer to 10 or more.
[0068] Under the same conditions, the more the surface of the secondary particles is staggered and stacked in flaky form, the more primary particles there are on the total surface, the better the cycle performance.
[0069] In an optional embodiment, in the positive electrode material precursor, the average roundness of the cross section of the secondary particles is not less than 0.95;
[0070] Optionally, the average roundness of the cross section of the secondary particles may be 0.95, 0.96, 0.97, 0.98, 0.99, 0.995, 0.999 or any value between 0.95 and 1.
[0071] In an optional embodiment, the average circularity is measured in a cross-sectional photograph of the secondary particles along the diameter direction at a magnification of 3000-5000 times.
[0072] In some embodiments, the average circularity at a magnification of 3000 times, 4000 times, 5000 times, or any value between 3000 and 5000 times.
[0073] Roundness is usually expressed as a numerical value, which reflects the sharpness or curvature of the edge of a graphic. The closer the roundness is to 1, the smoother the surface of the object is and the closer the shape is to a theoretical circle.
[0074] The calculation formula is: roundness = 4π*area / (circumference 2 ).
[0075] like Figure 1 As shown, a largest and most complete secondary particle spherical cross-section (right) was selected from the cross-section SEM photograph of the secondary particle (left), and then the area and perimeter of the cross-section were measured using Image J software.
[0076] The average roundness is the arithmetic average of multiple roundnesses measured from cross-sectional photographs of multiple secondary particles. The higher the average roundness, the fewer primary particle stacking defects on the surface of the secondary particles, the better the structural stability, and the more effective it is in suppressing cracks in the cathode material precursor when it is under pressure, thus improving the cycle performance.
[0077] Optionally, the cathode material precursor satisfies at least one of the following conditions:
[0078] A. The primary particles on the surface of the secondary particles are flaky, and the thickness of the primary particles on the surface is less than 60nm;
[0079] Optionally, the thickness of the primary particles on the surface of the secondary particles can be any value of <60nm, <55nm, <50nm, <45nm, <40nm, <35nm, <30nm, <25nm, <20nm, <15nm, <10nm or <60nm.
[0080] The method for measuring the thickness of the primary particles on the surface of secondary particles is: select the SEM partial magnified photo of the surface of the secondary particles with the maximum magnification, and then use the electronic ruler software ruler to measure the ruler length and the shortest distance between the two ends of another plane adjacent to the edge of the large plane in the selected surface primary particles, and convert it to obtain the thickness value. The larger the magnification of the SEM, the higher the measurement accuracy.
[0081] B. The average angle γ between the primary particle and the tangent plane of the secondary particle's sphere is ≤10°;
[0082] Optionally, the average angle γ between the primary particle on the surface of the secondary particle and the tangent plane of the sphere of the secondary particle can be 10°, 9°, 8°, 7°, 6°, 5°, 4°, 5°, 2°, 1°, 0°, or any value less than or equal to 10°.
[0083] The schematic diagram of the angle between the primary particle and the tangent plane of the secondary particle's sphere is as follows: Figure 2 The average angle is the arithmetic mean of multiple angles. The average angle γ≤10° indicates that the primary particles are in a state of dislocation and stacking on the surface of the secondary particles, which is similar to "duckweed", attached to the surface of the secondary particles, but there may be a small angle between them and the tangent plane.
[0084] Controlling the average angle also helps the expansion and contraction direction of the primary particles on the surface to be more parallel to the cross-section of the secondary particle sphere during charge and discharge, thereby inhibiting the generation of cracks that penetrate the surface and improving the cycle performance.
[0085] C. When the width of the notch on the edge of the cut surface of the secondary particle is b, the maximum depth of the notch on the edge of the cut surface of the secondary particle is h≤0.5b;
[0086] Optionally, the maximum depth h of the notch at the edge of the cut surface of the secondary particle may be 0.1b, 0.2b, 0.3b, 0.4b, 0.5b or any value of h≤0.5b.
[0087] The purpose of controlling the notch size at the edge of the cut surface is to control the stacking defects of the primary particles on the surface of the secondary particles and to inhibit cracks from forming when the cathode material precursor is under pressure.
[0088] Select two endpoints with the same length from the center of the circle to the edge of the notch, and set the length of the line connecting the two endpoints of the notch to the width b of the cut surface edge notch; set the longest line between the point perpendicular to the width line and the bottom of the notch to the maximum depth h.
[0089] Measurement diagram Figure 3The left picture is a SEM photo of the cross section of the secondary particle, and the right picture is a partial SEM photo of the cross section of the secondary particle. The edge notch width b of the cross section in the right picture is measured to be 25nm, and the maximum depth h is 7.5nm, that is, h=0.3b≤0.5b.
[0090] D. The secondary particles are densely arranged inside, and the porosity of the secondary particles is 2%-6%;
[0091] Optionally, the secondary particles are arranged in a non-radially dense manner internally;
[0092] Optionally, the porosity of the secondary particles may be 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, or any value between 2% and 6%;
[0093] The porosity of the secondary particles is measured by selecting a largest and most complete secondary particle spherical cross section from the cross-section SEM photograph of the secondary particles, and then using Image J software to measure the porosity of the cross section.
[0094] Compared with the radial structure, the internal non-radial arrangement is less likely to cause through-cracks caused by radial cracking; the internal dense arrangement can greatly reduce the internal stress accumulation of the precursor.
[0095] E. The cathode material precursor has pores inside, and the pore diameter is ≤30nm;
[0096] Optionally, the pore diameter of the internal pores can be 30nm, 29nm, 28nm, 27nm, 26nm, 25nm, 24nm, 23nm, 22nm, 21nm, 20nm, 18nm, 16nm, 14nm, 12nm, 10nm, 8nm, 6nm, 4nm, 2nm, 1nm or any value ≤30nm.
[0097] The method for measuring the internal pore diameter is: select the largest and most complete secondary particle spherical section from the partial SEM magnified photo of the secondary particle section, and then use the electronic ruler software ruler to measure the ruler length and the longest distance between the two ends of the selected hole, and convert it to get the pore diameter value. The larger the SEM magnification, the higher the measurement accuracy.
[0098] The interior of the positive electrode material precursor prepared in the present application is mainly micropores and mesopores, with fewer macropores, which makes the structure more stable, has better pressure-bearing performance, and has a higher compaction density, which can further improve the capacity performance of the material; it can also effectively avoid intergranular cracks caused by anisotropic volume changes during charging and discharging, thereby improving the cycle performance.
[0099] In an optional embodiment, the cathode material precursor satisfies at least one of the following conditions:
[0100] (1) The BET of the cathode material precursor is 16-20m 2 / g;
[0101] The appropriate amount of pores on the surface of the secondary particles not only prevents surface cracks from occurring, but also facilitates the infiltration of the electrolyte, thereby improving the reaction activity and capacity.
[0102] Optionally, the BET of the cathode material precursor may be 16m 2 / g, 17m 2 / g, 18m 2 / g, 19m 2 / g, 20m 2 / g or 16-20m 2 Any value between / g.
[0103] (2) TD of cathode material precursor is 2.2-2.5 g / cm 3 ;
[0104] The higher the tap density, the higher the volumetric specific capacity of the positive electrode material that inherits the precursor.
[0105] Optionally, the TD of the cathode material precursor may be 2.2 g / cm 3 , 2.25g / cm 3 , 2.3g / cm 3 , 2.35g / cm 3 , 2.4g / cm 3 , 2.45g / cm 3 , 2.5g / cm 3 or 2.2-2.5g / cm 3 Any value in between.
[0106] (3) (D90-D10) / D50 of the cathode material precursor is 1.2-1.8; the particle size D50 of the cathode material precursor is 10-20 μm;
[0107] Optionally, (D90-D10) / D50 of the positive electrode material precursor can be 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8 or any value between 1.2-1.8; the particle size D50 of the positive electrode material precursor can be 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm or any value between 12-20μm.
[0108] (4) The chemical formula of the cathode material precursor is Ni a M 1-a(OH)2, wherein 0.9≤a<1, M is at least one of Co, Mn, Al, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb, Sr; preferably M is Zr.
[0109] The higher the Ni content, the more electrons are transferred and the larger the capacity.
[0110] Preferably, doping with Zr element can stabilize the crystal structure of the material and improve the cycle stability of the material.
[0111] Optionally, a can be 0.900, 0.901, 0.902, 0.903, 0.904, 0.905, 0.906, 0.907, 0.908, 0.909, 0.910, 0.911, 0.912, 0.913, 0.914, 0.915, 0.916, 0.917, 0.918, 0.919, 0.920, 0.921, 0.922, 0.923, 0.924. 4. 0.925, 0.926, 0.927, 0.928, 0.929, 0.930, 0.931, 0.932, 0.933, 0.934, 0.935, 0.936, 0.937, 0.938, 0.939, 0.940, 0.941, 0.942, 0.943, 0.944, 0.945, 0.946, 0.947, 0.948, 0.949, 0.95 0, 0.951, 0.952, 0.953, 0.954, 0.955, 0.956, 0.957, 0.958, 0.959, 0.960, 0.961, 0.962, 0.963, 0.964, 0.965, 0.966, 0.967, 0.968, 0.969, 0.970, 0.971, 0.972, 0.973, 0.974, 0.975, 0.976 6. 0.977, 0.978, 0.979, 0.980, 0.981, 0.982, 0.983, 0.984, 0.985, 0.986, 0.987, 0.988, 0.989, 0.990, 0.991, 0.992, 0.993, 0.994, 0.995, 0.996, 0.997, 0.998, 0.999, or any value greater than or equal to 0.9 and less than 1.
[0112] The present application also provides a method for preparing a positive electrode material precursor, comprising:
[0113] Adding a metal salt solution including a nickel salt and / or a doped metal salt, a precipitant and a complexing agent into the first base solution, and performing a first continuous coprecipitation reaction under an inert atmosphere to obtain a seed crystal;
[0114] The seed crystal, the precipitant and the complexing agent are added into the second base liquid, and a second continuous co-precipitation reaction is carried out under an inert atmosphere, and a positive electrode material precursor is obtained by post-processing.
[0115] In an optional embodiment, the method for preparing the positive electrode material precursor satisfies at least one of the following conditions:
[0116] a. The total metal ion concentration of the metal salt solution is 1-5 mol / L;
[0117] Optionally, the total metal ion concentration of the metal salt solution may be 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L or any value between 1 and 5 mol / L;
[0118] b. The metal salt includes one or more of sulfate, nitrate, acetate and chloride; the ratio of nickel to the total molar amount of the metal is (0.9-1):1;
[0119] c. The doping metal M in the doping metal salt includes at least one of Co, Mn, Al, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb, and Sr;
[0120] d. The doped metal salt is a zirconium salt, and a buffer is added to the zirconium salt, wherein the buffer includes sodium citrate and / or trisodium citrate;
[0121] e. The complexing agent includes one or more of ammonia water, ammonium bicarbonate, and ammonium carbonate, and the concentration of the complexing agent is 2-20 mol / L; the complexing agent is preferably ammonia water, and the ammonia concentration in the first coprecipitation reaction and the second coprecipitation reaction is independently 2-17 g / L; the ammonia concentration refers to the NH4 + concentration;
[0122] Optionally, the concentration of the complexing agent can be 2mol / L, 3mol / L, 4mol / L, 5mol / L, 6mol / L, 7mol / L, 8mol / L, 9mol / L, 10mol / L, 11mol / L, 12mol / L, 13mol / L, 14mol / L, 15mol / L, 16mol / L, 17mol / L, 18mol / L, 19mol / L, 20mol / L or any value between 2-20mol / L; the ammonia concentration of the system can be 2g / L, 3g / L, 4g / L, 5g / L, 6g / L, 7g / L, 8g / L, 9g / L, 10g / L, 11g / L, 12g / L, 13g / L, 14g / L, 15g / L, 16g / L, 17g / L or any value between 2-17g / L;
[0123] f. The precipitant includes one or more of sodium hydroxide, potassium hydroxide, and lithium hydroxide, and the concentration of the precipitant is 2-20 mol / L;
[0124] Optionally, the concentration of the precipitant can be 2mol / L, 3mol / L, 4mol / L, 5mol / L, 6mol / L, 7mol / L, 8mol / L, 9mol / L, 10mol / L, 11mol / L, 12mol / L, 13mol / L, 14mol / L, 15mol / L, 16mol / L, 17mol / L, 18mol / L, 19mol / L, 20mol / L or any value between 2-20mol / L;
[0125] g. The first base liquid and the second base liquid are each independently water or a mixed aqueous solution containing an aqueous complexing agent and a precipitant.
[0126] In an optional embodiment, the method for preparing a lithium-ion battery positive electrode material precursor satisfies at least one of the following conditions:
[0127] h. The particle size D50 of the seed crystal is 2-8 μm;
[0128] Optionally, the particle size D50 of the seed crystal may be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm or any value between 2 and 8 μm;
[0129] i. The ratio of seed crystals added is 0.5wt%-5.0wt% of the yield of the second continuous coprecipitation reaction;
[0130] Optionally, the proportion of seed crystals is 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2.0wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt% %, 2.8wt%, 2.9wt%, 3.0wt%, 3.1wt%, 3.2wt%, 3.3wt%, 3.4wt%, 3.5wt%, 3.6wt%, 3.7wt%, 3.8wt%, 3.9wt%, 4.0wt%, 4.1wt%, 4.2wt%, 4.3wt%, 4.4wt%, 4.5wt%, 4.6wt%, 4.7wt%, 4.8wt%, 4.9wt%, 5.0wt% or any value between 0.5wt% and 5.0wt%;
[0131] j. The temperature of the first continuous coprecipitation reaction and the second continuous coprecipitation reaction are independently 35-75 ° C, and the stirring speed is 200-1200r / min; preferably 200-800r / min;
[0132] Optionally, the temperature of the first continuous coprecipitation reaction and the second continuous coprecipitation reaction can be independently 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or any value between 35-75°C, and the stirring speed can be 200r / min, 300r / min, 400r / min, 500r / min, 600r / min, 700r / min, 800r / min, 900r / min, 1000r / min, 1100r / min, 1200r / min or any value between 200-1200r / min;
[0133] k. The pH value of the first continuous coprecipitation reaction is 11.4-12.4; the pH value of the second continuous coprecipitation reaction system is 11.0-12.0;
[0134] Optionally, the system pH of the first continuous coprecipitation reaction may be 11.4, 11.5, 11.6, 11.7, 11.8, 11.9, 12.0, 12.1, 12.2, 12.3, 12.4 or any value between 11.4 and 12.4;
[0135] Optionally, the system pH of the second continuous coprecipitation reaction may be 11.0, 11.1, 11.2, 11.3, 11.4, 11.5, 11.6, 11.7, 11.8, 11.9, 12.0 or any value between 11.0 and 12.0;
[0136] 1. Post-processing includes washing, solid-liquid separation, solid drying and screening for demagnetization.
[0137] By limiting the temperature, pH value and ammonia concentration during the reaction process, a cathode material precursor having the special morphology of the present application can be better obtained.
[0138] The present application also provides a positive electrode material for a lithium-ion battery. The raw materials of the positive electrode material for a lithium-ion battery include a positive electrode material precursor.
[0139] The present application also provides a lithium-ion battery, including a lithium-ion battery positive electrode material.
[0140] The present application also provides a lithium battery device, including a lithium-ion battery.
[0141] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0142] Example 1
[0143] This embodiment provides a positive electrode material precursor with a staggered and flat stack, the molecular formula of which is Ni 0.99 Zr 0.01 (OH)2, the preparation method thereof comprises the following steps:
[0144] ① Solution preparation: accurately weigh nickel sulfate and zirconium sulfate according to the molar ratio of nickel to zirconium of 99.9:0.01, and add them into two dissolution tanks respectively. Add pure water to nickel sulfate and stir until it is completely dissolved to prepare a nickel sulfate solution with a concentration of 2 mol / L; add sodium citrate and concentrated sulfuric acid to zirconium sulfate and stir until it is completely dissolved to prepare a zirconium sulfate solution with a concentration of 3.65 g / L; prepare a precipitant of 10 mol / L sodium hydroxide solution and a complexing agent of 8 mol / L ammonia solution.
[0145] ② Preparation of seed crystals: Add 80% of the available volume of the reactor into the reactor (I), heat to 60°C, control the stirring speed at 710r / min, and introduce nitrogen protection. When the conditions are met, simultaneously introduce a nickel sulfate solution with a flow rate of 4.0-4.3% / h of the available volume of the reactor, a zirconium sulfate solution with a flow rate of 0.9-1.1% / h of the available volume of the reactor, a sodium hydroxide solution with a flow rate of 1.4-1.5% / h of the available volume of the reactor, and an ammonia solution with a flow rate of 0.22-0.25% / h of the available volume of the reactor. The pH value during the first continuous coprecipitation reaction is controlled to be 11.8-12.1 and the ammonia concentration is 3.8-4.2g / L. The reaction nucleation amount is controlled until the seed slurry particle size D50 is stably controlled at 3.0±0.5μm, then start to add the seed slurry, and store the seed slurry under nitrogen.
[0146] ③ Preparation of continuous growth reactor products: in the reactor (Ⅱ), the stirring speed is controlled at 250r / min, nitrogen is introduced for protection, 80% of the available volume of the reactor is added with seed slurry, the ammonia concentration is adjusted to 10.4-11.0g / L and the pH value is 11.1-11.4, the temperature is raised to 60°C, and then a nickel sulfate solution with a flow rate of 4.0-4.3% / h of the available volume of the reactor and a sulfuric acid solution with a flow rate of 1.0-1.2% / h of the available volume of the reactor are introduced simultaneously. The zirconium solution, the ammonia solution with the available volume of the reactor of 0.46-0.48% / h, the sodium hydroxide solution with the available volume of the reactor of 1.4-1.5% / h, the amount of seed crystal added per hour is 4.5wt% of the hourly output; and the pH value in the second continuous coprecipitation reaction process is controlled to be 11.5-11.7, the ammonia concentration is 10.8-11.2g / L, and after the D50 is stably controlled at 13.7±1μm, the material is continuously and stably output and collected.
[0147] ④ After centrifugation, the material is washed with alkali and water, and the washed solid particles are dried and sieved to remove magnetism, thus obtaining a high-nickel precursor with multiple flaky primary particles stacked flat on the surface. The surface SEM photos and the enlarged surface SEM photos are shown in the figure. Figure 4 and Figure 5 shown.
[0148] Example 2
[0149] This embodiment provides a positive electrode material precursor with a staggered and flat stack, the molecular formula of which is Ni 0.95 Al 0.03 Mn 0.02 (OH)2, the preparation method thereof comprises the following steps:
[0150] ① Solution preparation: accurately weigh nickel sulfate, aluminum sulfate and manganese sulfate according to the molar ratio of nickel, aluminum and manganese of 95:3:2, add them to the dissolution tank, add pure water and stir until completely dissolved, and prepare a mixed metal salt solution with a concentration of 2 mol / L;
[0151] ② Preparation of seed crystals: Add 80% of the available volume of the reactor into the reactor (I), heat to 50°C, control the stirring speed at 650r / min, and introduce nitrogen protection. When the conditions are met, simultaneously introduce a mixed metal salt solution with a flow rate of 3.9-4.1% / h of the available volume of the reactor, a sodium hydroxide solution with a flow rate of 0.14-0.16% / h of the available volume of the reactor, and an ammonia solution with a flow rate of 0.40-0.43% / h of the available volume of the reactor. Control the pH value of the first continuous coprecipitation reaction process to be 12.0-12.3 and the ammonia concentration to be 4.0-4.5g / L, control the reaction nucleation amount, and start to add the seed slurry when the particle size D50 of the seed slurry is stably controlled at 7.0±0.5μm, and store the seed slurry under nitrogen.
[0152] ③ Preparation of continuous growth kettle products: In the reactor (Ⅱ), the stirring speed is controlled at 350r / min, nitrogen protection is introduced, 80% of the available volume of the reactor is added with seed slurry, the ammonia concentration is adjusted to 13.4-13.9g / L and the pH value is 11.5-11.8, the temperature is raised to 50°C, and then a mixed metal salt solution with a flow rate of 4.0-4.2% / h of the available volume of the reactor, an ammonia solution with a flow rate of 0.42-0.45% / h of the available volume of the reactor, and a sodium hydroxide solution with a flow rate of 1.48-1.50% / h of the available volume of the reactor are introduced simultaneously, and the amount of seed added per hour is 0.5wt% of the hourly output; and the pH value is controlled to be 11.8-12.1 and the ammonia concentration is 13.6-14.0g / L during the second continuous coprecipitation reaction. After D50 is stably controlled at 10.0±0.5μm, the material is continuously and stably produced and collected.
[0153] ④ After centrifugation, the material is washed with alkali and water, and the washed solid particles are dried and sieved to remove magnetism, thus obtaining a high nickel-doped precursor. The surface SEM photos and the surface partial magnified SEM photos are shown in FIG. Figure 6 and Figure 7 As shown in Figure 1, multiple flaky primary particles are stacked in a staggered manner, and the edges of multiple flaky primary particles are fused to form larger flaky particles. The cross-sectional SEM photo is shown in Figure 1. Figure 8 shown.
[0154] Comparative Example 1
[0155] This comparative example provides a high nickel-doped precursor with a molecular formula of Ni 0.95 Al 0.03 Mn 0.02 (OH)2; the preparation method is as follows:
[0156] ① Solution preparation: accurately weigh nickel sulfate, aluminum sulfate and manganese sulfate according to the molar ratio of nickel, aluminum and manganese of 95:3:2, add them to the dissolution tank, add pure water and stir until completely dissolved, and prepare a mixed metal salt solution with a concentration of 2 mol / L;
[0157] ② Preparation of seed crystals: Add 80% of the available volume of the reactor into the reactor (I), heat to 60°C, control the stirring speed at 700r / min, and introduce nitrogen protection. When the conditions are met, simultaneously introduce a mixed metal salt solution with a flow rate of 4.0-4.2% / h of the available volume of the reactor, a sodium hydroxide solution with a flow rate of 1.45-1.48% / h of the available volume of the reactor, and an ammonia solution with a flow rate of 0.40-0.43% / h of the available volume of the reactor. Control the pH value of the first continuous coprecipitation reaction process to be 11.9-12.2 and the ammonia concentration to be 4.0-4.5g / L, control the reaction nucleation amount, and start to add the seed slurry when the particle size D50 of the seed slurry is stably controlled at 7.0±0.5μm, and store the seed slurry under nitrogen.
[0158] ③ Preparation of continuous growth kettle products: In the reactor (Ⅱ), the stirring speed is controlled at 250r / min, nitrogen protection is introduced, 80% of the available volume of the reactor seed slurry is added, the ammonia concentration is adjusted to 3.0-3.3g / L and the pH value is 10.6-10.8, the temperature is raised to 60°C, and then a mixed metal salt solution with a flow rate of 4.0-4.2% / h of the available volume of the reactor, an ammonia solution with a flow rate of 0.08-0.09% / h of the available volume of the reactor, and a sodium hydroxide solution with a flow rate of 1.47-1.50% / h of the available volume of the reactor are introduced simultaneously, and the amount of seed added per hour is 0.5wt% of the hourly output; and the pH value is controlled to be 10.6-10.90 and the ammonia concentration is 3.5-4.0g / L during the second continuous coprecipitation reaction. After D50 is stably controlled at 10±0.5μm, the material is continuously and stably produced and collected.
[0159] ④ After centrifugation, the material is washed with alkali and water, and the washed solid particles are dried and sieved to remove magnetism, thus obtaining a high nickel-doped precursor with a wide radial grain morphology distribution. The surface SEM photo is as follows: Fig. 9 As shown, the cross-section SEM photo is as follows Fig.10 shown.
[0160] Comparative Example 2
[0161] This comparative example provides a medium-low nickel precursor with a molecular formula of Ni 0.49 Co 0.215 Mn 0.295 (OH)2; the preparation method is as follows:
[0162] ① Solution preparation: accurately weigh nickel sulfate, cobalt sulfate and manganese sulfate according to the molar ratio of nickel, cobalt and manganese of 0.49:0.215:0.295, add them to the dissolution tank, add pure water and stir until completely dissolved, and prepare a mixed metal salt solution with a concentration of 2 mol / L;
[0163] ② Preparation of continuous products: Add 80% of the available volume of the reactor into the reactor with water, control the stirring speed at 300r / min, add 0.36% of the available volume of the reactor with ammonia solution and 0.09% of the available volume of the reactor with sodium hydroxide solution, adjust the ammonia concentration of the reaction bottom liquid to 8.9-9.3g / L and the pH value to 10.9-11.2, raise the temperature to 40°C, and then simultaneously introduce a mixed metal salt solution with a flow rate of 4.4-4.6% / h of the available volume of the reactor, an ammonia solution with a flow rate of 0.27-0.30% / h of the available volume of the reactor, and a sodium hydroxide solution with a flow rate of 1.34-1.36% / h of the available volume of the reactor; and control the pH value to 10.9-11.20 and the ammonia concentration to 9.0-9.5g / L during the second continuous coprecipitation reaction, and after the product D50 is stably controlled at 9.5±0.5μm, continuously and stably output the material and collect it.
[0164] ③ After centrifugation, the material is washed with alkali and water, and the washed solid particle material is dried and sieved to remove magnetism, so as to obtain a medium-low nickel precursor with a wide distribution of hexagonal nanosheet morphology. The surface SEM photos and the surface local enlarged SEM photos are shown in Fig.11 and Fig.12 The cross-sectional SEM images are shown in Fig.13 shown.
[0165] For all the above embodiments and comparative samples, lithium hydroxide and high nickel doped precursor were mixed evenly in a high mixer at a molar ratio of 1.07:1, and the high nickel doped positive electrode material was obtained by sintering at 680°C for 5h. The high nickel doped positive electrode material was tested for electrochemical performance using a button-type semi-electric: the above positive electrode material, conductive carbon black, and binder PVDF (polyvinylidene fluoride) were mixed into a slurry at a ratio of 8:1:1, and coated on aluminum foil to make a positive electrode sheet. The negative electrode sheet used a metal lithium sheet, and the electrolyte used 1mol / L LiPF6 / EC:DMC (volume ratio 1:1). The battery shell, positive and negative electrode sheets, diaphragms, springs, and gaskets were assembled into button batteries in a vacuum glove box. The electrochemical performance test was carried out using a blue electric test system at 25°C and a voltage of 3.0-4.3V.
[0166] The test results of Examples 1-2 and Comparative Examples 1-2 are shown in Table 1:
[0167] Table 1 Test results
[0168]
[0169] Note: 1. When all the notches on the edge of the cut surface meet the condition h≤0.5b, fill in h≤0.5b; if there is only one notch on the edge of the cut surface that does not meet the condition h≤0.5b, fill in h>0.5b;
[0170] 2. Span = (D90-D10) / D50.
[0171] The surface of the secondary particles prepared in this embodiment 1-2 is formed by a plurality of flaky primary particles being stacked in a staggered manner, so that the secondary particles have a larger force-bearing area, and can quickly transfer the force to the lower primary particles when subjected to external force, thereby solving the problem of the secondary particle balls being easy to crack, ensuring the specific capacity of the material and improving the cyclic stability of the material. It can be seen from the surface SEM photo of embodiment 2 that the edges of the plurality of flaky primary particles are fused to form larger flaky particles, and the thickness thereof is thinner than that of the flaky primary particles of embodiment 1, which is more conducive to the complete infiltration and reaction of the electrolyte, and can slightly increase the battery capacity.
[0172] Comparative Example 1 uses a high nickel precursor prepared by a traditional continuous method, and the cross section is a radial structure, which is easy to produce through cracks during preparation; and after sintering into a positive electrode material, it is also easy to produce large radial cracks during charging and discharging, and its cycle capacity retention rate is significantly lower than that of Examples 1-2; Comparative Example 2 is a hexagonal nanosheet stack, and its sphericity in SEM is slightly poor, because the primary particles are thicker, which is not conducive to the infiltration of the electrolyte, and the nickel content is low, showing a low battery capacity; and there is a certain amount of fine primary particles in the figure, which is easy to produce micropowder, and the cycle capacity retention rate is slightly lower than that of Examples 1-2. In Examples 1-2, the core-shell structure of the seed crystal with de-micronized powder and the smooth disc shape formed by the surface stacking have a wide particle size distribution and a high tap density, which not only has a high discharge capacity, but also has a high cycle retention rate.
[0173] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0174] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A cathode material precursor, characterized in that: The secondary particles of the positive electrode material precursor are formed by the aggregation of multiple primary particles. The primary particles on the surface of the secondary particles are in the form of flakes. The surface of the secondary particles includes multiple flake primary particles that are staggered and stacked.
2. The cathode material precursor according to claim 1, characterized in that: The average roundness of the cross section of the secondary particles is not less than 0.95; Optionally, the average roundness is measured in a cross-sectional photograph of the secondary particles along the diameter direction at a magnification of 3000-5000 times.
3. The cathode material precursor according to claim 1, characterized in that: At least one of the following conditions is met: A. The primary particles on the surface of the secondary particles are in the form of flakes, and the thickness of the primary particles on the surface is less than 60 nm; B. The average angle γ between the primary particles on the surface of the secondary particles and the tangent plane of the sphere of the secondary particles is ≤10°; C. When the width of the notch at the edge of the cut surface of the secondary particle is b, the maximum depth of the notch at the edge of the cut surface of the secondary particle is h≤0.5b; D. The secondary particles have pores inside, and the pore diameter is ≤30 nm; E. The secondary particles are densely arranged inside.
4. The cathode material precursor according to any one of claims 1 to 3, characterized in that: At least one of the following conditions is met: (1) The BET of the cathode material precursor is 16-20 m 2 / g; (2) The TD of the positive electrode material precursor is 2.2-2.5 g / cm 3 ; (3) (D90-D10) / D50 of the positive electrode material precursor is 1.2-1.8; the particle size D50 of the positive electrode material precursor is 10-20 μm; (4) The chemical formula of the positive electrode material precursor is Ni a M 1-a (OH)2, wherein 0.9≤a<1, and M is at least one of Co, Mn, Al, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb, and Sr.
5. A method for preparing a cathode material precursor according to any one of claims 1 to 4, characterized in that: include: Adding a metal salt solution including a nickel salt and / or a doped metal salt, a precipitant and a complexing agent into the first base solution, and performing a first continuous coprecipitation reaction under an inert atmosphere to obtain a seed crystal; The seed crystal, the precipitant and the complexing agent are added to the second base liquid, and a second continuous co-precipitation reaction is carried out under an inert atmosphere, and the positive electrode material precursor is obtained by post-processing.
6. The method for preparing a cathode material precursor according to claim 5, characterized in that: At least one of the following conditions is met: a. The total metal ion concentration of the metal salt solution is 1-5 mol / L; b. The metal salt includes one or more of sulfate, nitrate, acetate, and chloride; the ratio of the total molar amount of nickel to the metal in the metal salt is (0.9-1):1; c. The doping metal M in the doping metal salt includes at least one of Co, Mn, Al, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb, and Sr; d. The doped metal salt is a zirconium salt; a buffer is added to the zirconium salt, the buffer comprising sodium citrate and / or trisodium citrate; e. The complexing agent includes one or more of ammonia, ammonium bicarbonate, and ammonium carbonate, and the concentration of the complexing agent is 2-20 mol / L; f. The precipitant comprises one or more of sodium hydroxide, potassium hydroxide and lithium hydroxide, and the concentration of the precipitant is 2-20 mol / L; g. The first base liquid and the second base liquid are each independently water or a mixed aqueous solution containing the complexing agent and the precipitant.
7. The method for preparing a cathode material precursor according to claim 5 or 6, characterized in that: At least one of the following conditions is met: h. The seed crystal particle size D50 is 2-8 μm; i. adding the seed crystals in a ratio of 0.5wt% to 5.0wt% of the yield of the second continuous coprecipitation reaction; j. The temperature of the first continuous coprecipitation reaction and the second continuous coprecipitation reaction are independently 35-75°C, and the stirring speed is 200-1200r / min; k. The pH value of the first continuous coprecipitation reaction is 11.4-12.4; the pH value of the second continuous coprecipitation reaction is 11.0-12.0; 1. The post-treatment includes washing, solid-liquid separation, solid drying and screening and demagnetization treatment.
8. A positive electrode material for a lithium ion battery, characterized in that: The raw material of the lithium-ion battery positive electrode material includes the positive electrode material precursor according to any one of claims 1 to 4.
9. A lithium ion battery, characterized in that: The lithium-ion battery positive electrode material comprises the positive electrode material of claim 8.
10. A lithium battery device, characterized in that: Includes the lithium ion battery as claimed in claim 9.